2004
DOI: 10.1016/j.ejcts.2004.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cardiopulmonary bypass on cortical cerebral oxygenation during coronary artery bypass grafting

Abstract: Objective: To investigate the changes in cerebral oxygenation during coronary artery bypass grafting (CABG) with normothermic cardiopulmonary bypass (CPB) using near infrared spectroscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Near-infrared light in the wavelength range between 700 and 1000 nm penetrates biologic tissue and bone, which makes transcranial measurements feasible. 13 The technique of NIRS has been used to evaluate cerebral cortical oxygenation changes during carotid surgery, 14 CABG, [15][16][17][18][19] and off-pump cardiopulmonary bypass surgery. 20 The clinical application of intracranial NIRS in adults has been hampered by concerns over contamination by extracranial tissues.…”
Section: Near-infrared Spectroscopymentioning
confidence: 99%
“…Near-infrared light in the wavelength range between 700 and 1000 nm penetrates biologic tissue and bone, which makes transcranial measurements feasible. 13 The technique of NIRS has been used to evaluate cerebral cortical oxygenation changes during carotid surgery, 14 CABG, [15][16][17][18][19] and off-pump cardiopulmonary bypass surgery. 20 The clinical application of intracranial NIRS in adults has been hampered by concerns over contamination by extracranial tissues.…”
Section: Near-infrared Spectroscopymentioning
confidence: 99%
“…During cardiopulmonary bypass, MAP may decrease to below 50 mmHg, and cerebral oxygenation becomes lowered in the initial period when laminar flow is introduced (Lassnigg et al ., ). In some patients, however, a reduction in cerebral oxygenation recovers only at termination of the cardiopulmonary bypass (Nollert et al ., ,b; Kadoi et al ., ; Lassnigg et al ., ; Talpahewa et al ., ), and in the present study, frontal lobe oxygenation was determined after spontaneous circulation was re‐established, inspired oxygen fraction was high and arterial CO 2 pressure was controlled within normal limits.…”
Section: Discussionmentioning
confidence: 74%
“…et al studied the changes in cortical cerebral oxygenation during ONCAB using the Near infrared spectroscopy. 56 They found that ONCAB is responsible for deterioration in [O 2 Hb], and cerebral blood volume, which peaks at 40-60 min following initiation of CPB. The changes in [O 2 Hb] are reversible whereas the reduction of cerebral blood volume persists to the end of the surgery.…”
Section: Lita Suture Successfulmentioning
confidence: 99%